Pengalaman Emosional Anak Usia Sekolah Melalui Menggambar di Bangsal Anak RS Dr.M.Djamil Padang: Emotional Experience of School-age Children Through Drawing in The Pediatric Ward of Dr.M.Djamil Hospital Padang - Dwi Novrianda; Devia Putri Lenggogeni (Fakultas Keperawatan Universitas Andalas, 2011)
Hospitalisation is often stressful for children and sometimes are not able to verbally expressed. Drawing is a non-verbal communication techniques that can be used for exploring the emotional experience of children who are hospitalised with a non-threatening way. The purpose of this study was to determine the emotional experience of school-age children through drawing on the children’s ward of Dr. M. Djamil Hospital in Padang. This study used qualitative methods with phenomenological approach. The study found three main themes: (1) a variety of reasons participants about the image created, (2) participants’ response to a pleasant experience, and (3) participants’ response to the sad and painful experience. It can be concluded that the expression of the emotional experience of school age children who are hospitalised through the drawing can deliver their thoughts and feelings and their response to emotional experience in the hospital something that is not fun.